Study on the Paths to Improve the Intercultural Competence of Foreign Language Teachers in Colleges and Universities under the Background of Globalization - Zhang, Weiyi (Journal of Educational Research and Policies, 2025)
Globalization has spurred college English education to pivot towards cultivating intercultural communicative competence, making it essential for teachers to enhance their intercultural teaching acumen. Currently, college English teachers face multiple intercultural-competence flaws, such as insufficient educational awareness, subpar communicative skills, a lack of unified curriculum content planning, and restricted research capabilities. To address these, improvement paths like academic immersion for awareness building, knowledge integration to refine the training system, and continuous learning to boost teaching proficiency can be pursued, which will aid teachers in improving intercultural competence and fostering intercultural teaching in college English.